Genetic and metabolic engineering - Yang,Yea-Tyng (Pontificia Universidad Católica de Valparaíso, 1998)
Recent advances in molecular biology techniques, analytical methods and mathematical tools have led to a growing interest in using metabolic engineering to redirect metabolic fluxes for industrial and medical purposes. Metabolic engineering is referred to as the directed improvement of cellular properties through the modification of specific biochemical reactions or the introduction of new ones, with the use of recombinant DNA technology (Stephanopoulos, 1999). This multidisciplinary field draws principles from chemical engineering, biochemistry, molecular and cell biology, and computational sciences. The aim of this article is to give an overview of the various strategies and tools available for metabolic engineers and to review some of the recent work that has been conducted in our laboratories in the metabolic engineering area.